Diethylstilbestrol implant plus oral Chlortetracycline vs. Oral Chlortetracycline alone for fattening steers - McCartor, M.M.; Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Hereford steers used in this study were fed in outdoor dirt lots without shelter. Each steer in lot 23, described in a trace-mineral study reported elsewhere in this publication, received a 24-mg. implant of diethylstilbestrol on the first day of the feeding period. Steers in both lots received 70 mgs. of oral chlortetracycline each day during the feeding period.
Keywords: Beef; Diethylstilbestrol implant; Chlortetracycline